Cervical spine involvement as initial manifestation of rheumatoid arthritis: a case report - Araújo, Filipe (2015)
Rheumatoid arthritis' synovitis affects mostly small hand and feet joints, although it may compromise any joint with a synovial lining. Cervical involvement occurs usually in longstanding disease in over half of these patients. We report the case of a 35-year old male patient who was referred to our outpatient clinic for a 2-year severe and disabling inflammatory neck pain, with incomplete response to intramuscular non-steroidal anti-inflammatory drugs and unremarkable cervical imaging studies. He also mentioned self-limited episodes of symmetric polyarthralgia involving hands, wrists, elbows, knees and feet, which started after his cervical complaints. On laboratorial workup, positive rheurriatoid factor and anti-citrullinated peptide antibody and negative HLA-B27 were found. Cervical spine magnetic resonance imaging revealed atlantoaxial subluxation and odontoid process inflammatory pannus and erosions. Rheumatoid arthritis with cervical spine involvement as initial manifestation of disease was the definite diagnosis. The patient was started on methotrexate and prednisone and he was referred to neurosurgery outpatient clinic for cervical spine fixation.